A Premium Taste from the Desert to the Table: A Marketing Case Study on Ilhamtaufiq Group Sdn Bhd - Suib, Fatin Husna; Saleem Subhani (IIUM Journal of Case Studies in Management, 2025)
Ilhamtaufiq Group Sdn Bhd is a Malaysian food importer and reseller founded during the COVID-19 pandemic 2019. Led by founder Muhammad Taufiq Firdaus Bin Ishak, the company built a niche in frozen fresh dates (Kurma Sejok), later expanding to products like Bilis Bersih (pre-cleaned anchovies), Turkish cherries, and seasonal mangoes. Its marketing strategy hinges on digital platforms such as TikTok, Instagram, and Facebook, supported by influencer partnerships, consistent paid advertising, and a vast agent network. Despite strong brand recall, the company faces challenges like competition from Arab traders, limited product availability due to seasonality, and reliance on high digital ad spend. This case study reviews existing goals, implementation tactics, and evaluation methods, while offering improvements in agent training, AI-based targeting, content personalization, and expanded year-round product lines. Ilhamtaufiq Group demonstrates how small businesses can carve out competitive space by combining cultural relevance, strategic digital execution, and emotional storytelling.